PENGARUH PEMBERIAN JUS DAUN TORBANGUN DENGAN PENINGKATAN PRODUKSI ASI PADA IBU NIFAS DI PMB NY. N KOTA BEKASI TAHUN 2022 - Aisyah, Yeki Supriaten (Politeknik Tiara Bunda, 2025)
Background Back: Breast milk (ASI) is the most recommended food for babies at least during their first 6 months of life. Breast milk production can be increased by consuming it Torbangun leaves. Because it is believed to increase prolactin and oxytocin levels, and contains nutrients that can be used as raw materials for breast milk synthesis. Objective Study : To determine the effect of giving decoction of Torbangun leaves on increasing breast milk in postpartum mothers. Method Study : This research is a quantitative type with a pre-experiment design whose design uses the one group pretest-posttest design, because this research aims to compare the results of the intervention group pretest and intervention posttest , the sample taken by purposive sampling was 21 postpartum mothers who had given birth. Results Research : The results of the paired sample t-test show a value of p = 0.000 < α = 0.05, this means that there is an effect of giving boiled Torbangun leaves on breast milk production in postpartum mothers. Conclusion : Based on the results of this study, it was found that there was an effect of giving boiled Torbangun leaves on increasing breast milk